1988
DOI: 10.1128/iai.56.6.1580-1584.1988
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies to Staphylococcus aureus laminin-binding proteins cross-react with mammalian cells

Abstract: We and others have previously shown that some microorganisms, including bacteria, express on their surfaces receptors that specifically recognize extracellular matrix proteins, such as laminin, fibronectin, or both. The ability of microorganisms to adhere and to invade might depend on the existence of receptors which could, thus, be correlated with pathogenicity. In the present paper, we report the isolation of five stable cell lines that were producers of monoclonal antibodies to Staphylococcus aureus laminin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The FM-binding receptor of S. aureus was sensitive to trypsin treatment and resistant to treatment with ,-galactosidase and sodium metaperiodate (Table 4), which suggests that the receptor has a protein component. At present it is unknown whether this mucin-binding receptor is similar to previously described surface proteins of S. aureus that mediate binding to fibrinogen (18), fibronectin (24), laminin (42), collagen (29), influenza A virus-infected and control cell monolayers (15,51), the Fc piece of immunoglobulins (22), or silicone polymers (4). Surface proteins of other bacteria have been reported as receptors for mucin binding.…”
Section: Discussionmentioning
confidence: 76%
“…The FM-binding receptor of S. aureus was sensitive to trypsin treatment and resistant to treatment with ,-galactosidase and sodium metaperiodate (Table 4), which suggests that the receptor has a protein component. At present it is unknown whether this mucin-binding receptor is similar to previously described surface proteins of S. aureus that mediate binding to fibrinogen (18), fibronectin (24), laminin (42), collagen (29), influenza A virus-infected and control cell monolayers (15,51), the Fc piece of immunoglobulins (22), or silicone polymers (4). Surface proteins of other bacteria have been reported as receptors for mucin binding.…”
Section: Discussionmentioning
confidence: 76%
“…The binding of heparan sulfate to S. aureus V8 does not appear to be mediated by any of the staphylococcal surface proteins so far described, since the Mrs of the heparan sulfate-binding proteins differ from those of other described staphylococcal adhesins. The apparent affinity of the heparan sulfate-binding proteins for their ligand is considerably lower than those of the staphylococcal adhesins which bind fibrinogen (4), fibronectin (25), laminin (20), collagen (27,30), and thrombospondin (15), which bind their respective ligands with dissociation constants of 10-9 M (10-7 M for collagen). The observation that the dissociation constant for the binding of heparan sulfate to S. aureus V8 is relatively high suggests that if the heparan sulfate-binding proteins are important in the pathogenesis of staphylococcal infections, they promote binding of the bacteria to host cells during early stages of the disease process.…”
Section: Resultsmentioning
confidence: 99%
“…Staphylococcus aureus and other staphylococcal species capable of causing diseases in humans and animals interact with various connective tissue proteins, such as fibronectin (25,29), collagens (27,30), laminin (20), and vitronectin (22). Although the consequences of these binding phenomena for host-parasite relationships are still to be explored, they could promote staphylococcal adherence to host tissues.…”
mentioning
confidence: 99%
“…It is well known that S. aureus binds to various substances existing on the surface of animal cells or tissues, such as fibronectin (10,16,29,31), laminin (10,18,22,31), type IV collagen (31), vitronectin (4), fibrinogen (3,10), and such bindings are considered to play an important role in early stages of bacterial infections (17,30). Generally, SpA is one of the major components of cell wall, for example, comprising 6.7%of the cell wall fraction of S. aureus Cowan I (9), and some previous studies suggested a possibility that SpA might play a role in bacterial binding to such substances (5,31).…”
Section: Discussionmentioning
confidence: 99%